2018
DOI: 10.1002/jcp.27939
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine aminotransferase promoted the proliferation and metastasis of non‐small cell lung cancer via upregulation of miR‐21

Abstract: The incidence and mortality of lung cancer ranked the first among all types of cancer in China, and non‐small cell lung cancer (NSCLC) is the most common type of lung cancer accounting for 85% of all lung cancers. Given that the survival rate of patients with advanced NSCLC is still poor nowadays, identification of novel therapeutic targets and the development of effective therapies are desired for the treatment of NSCLC in clinics. In this study, we reported the upregulation of ornithine aminotransferase (OAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The role of P5CS is likely to be context-specific, as, in breast cancer, CRISPR/Cas9-mediated knockout of P5CS had no impact on tumor growth, but it sensitized cancer cells to pharmacological inhibition of lipogenesis, indicating that inhibition of proline biosynthesis could synergize with therapies targeting lipid metabolism 122 . Recently, increased expression of OAT has been shown to correlate with NSCLC progression, and OAT activity supports proliferation and metastatic spread of NSCLC cells 126 .…”
Section: Other Proline Enzymesmentioning
confidence: 99%
“…The role of P5CS is likely to be context-specific, as, in breast cancer, CRISPR/Cas9-mediated knockout of P5CS had no impact on tumor growth, but it sensitized cancer cells to pharmacological inhibition of lipogenesis, indicating that inhibition of proline biosynthesis could synergize with therapies targeting lipid metabolism 122 . Recently, increased expression of OAT has been shown to correlate with NSCLC progression, and OAT activity supports proliferation and metastatic spread of NSCLC cells 126 .…”
Section: Other Proline Enzymesmentioning
confidence: 99%
“…A manual investigation of the GSMM flux profiles revealed three likely reasons for the essentiality of ASL : 1) compromised proline synthesis via OAT accompanied by 2) decreased fumarate production for the TCA cycle and 3) decreased OAA to aspartate conversion that compromises aminotransferase activity and therefore anaplerotic fueling of the TCA cycle. In addition to ASL, we identified six other significant targets from the gene essentiality analysis, most of which have been associated with poor cancer survival 6 , 43 45 . For example, increased expression of the IDH2 gene has been shown to be overexpressed in endometrial, prostate, testicular, and advanced colon cancer 46 48 , and we have recently demonstrated that IDH2 indeed fuels reductive glutaminolysis and fatty acid synthesis in the D492 and D492M cells in an accompanying study 49 .…”
Section: Discussionmentioning
confidence: 99%
“…38 OAT stimulated the proliferation, migration, and invasion and blocked the apoptosis, while the lack of OAT reduced the growth and metastasis of lung cancer xenograft. 39 Hence, P4 reduction of OAT levels may be beneficial in terms of growth and invasion suppression in GBM. Three hundred µM P4 increased the levels of the mitochondrial ATP synthase subunit beta (ATP5F1B, UniProt ID: P06576).…”
Section: Proteins Of Energy Metabolism Influenced By P4mentioning
confidence: 99%